Genome-wide analysis of genetic loci and candidate genes related to teat number traits in Dongliao black pigs - Ke, Juan; Chen, Changyi; Fei, Junwen; Luo, Ke; Cheng, Yu; Yu, Huimin; Cheng, Chao; Yan, Yiqing; Zhang, Xiaoran; Liang, Shuang; Sun, Hao; Bai, Chunyan; et al. (Frontiers in Genetics, 2025)
This study investigated the genetic basis of teat number variation in Dongliao black pigs. A total of 765 pigs were genotyped using the Porcine 50K SNP chip, and their teat numbers were recorded. Heritability estimates for total teat number (TTN) and teat pair number (TPN) were 0.091 and 0.097, respectively. Genome-wide association studies identified 74 significant SNPs for TTN and 105 for TPN. Nine candidate genes related to the teat number were identified: CSNK1G1, PLEKHM2, CABLES1, SLC25A21, RYR3, PIGH, GUCY1A1, RAPGEF2, and TRPC4AP. These findings provide insights into the genetic architecture of teat number variation in Dongliao black pigs.